Oligopyrimidine Tract at the 5' End of Mammalian Ribosomal Protein mRNAs is Required for their Translational Control - Levy, Sary; Avni, Dror; Hariharan, Narayanan; Perry, Robert P.; Meyuhas, Oded (Proceedings of the National Academy of Sciences - PNAS, 1991)
Mammalian ribosomal protein (rp) mRNAs are subject to translational control, as illustrated by their selective release from polyribosomes in growth-arrested cells and their underrepresentation in polysomes in normally growing cells. In the present experiments, we have examined whether the translational control of rp mRNAs is attributable to the distinctive features of their 5' untranslated region, in particular to the oligopyrimidine tract adjacent to the cap structure. Murine lymphosarcoma cells were transfected with chimeric genes consisting of selected regions of rp mRNA fused to non-rp mRNA segments, and the translational efficiency of the resulting chimeric mRNAs was assessed in cells that either were growing normally or were growth-arrested by glucocorticoid treatment. We observed that translational control of rpL32 mRNA was abolished when its 5' untranslated region was replaced by that of β-actin. At the same time, human growth hormone (hGH) mRNA acquired the typical behavior of rp mRNAs when it was preceded by the first 61 nucleotides of rpL30 mRNA or the first 29 nucleotides of rpS16 mRNA. Moreover, the translational control of rpS16-hGH mRNA was abolished by the substitution of purines into the pyrimidine tract or by shortening it from eight to six residues with a concomitant cytidine → uridine change at the 5' terminus. These results indicate that the 5'-terminal pyrimidine tract plays a critical role in the translational control mechanism. Possible factors that might interact with this translational cis regulatory element are discussed.